Evaluation Of Lampung Click Clicking Development - Prasetyorini Prasetyorini; Rellya Runasari; Rachmat Dody Ariesna (Penerbit Jurnal Indonesia, 2022)
FPTI (Indonesian Rock Climbing Federation), the administrator of the Lampung branch, is an organization engaged in rock climbing. This study intends to find out how to develop athletes at FPTI Lampung. The descriptive evaluative research method uses the CIPP (Contex, Input, Process, and Product) model. The population in this study were FPTI Lampung administrators, trainers and athletes of FPTI Lampung. The data source sample was selected purposively, namely by selecting people who are considered to know about the focus of the problem in depth and can be trusted to be used as data sources. Then it is combined with the snowball sampling technique, which is asking the previous informant to show other people who can be used as the next informant. Based on the results of data analysis conducted by researchers, the results of the study indicate that the government's support, both morally and materially, in sports development, especially rock climbing has a major influence on the resulting achievements. In rock climbing sports, the program has not been fully carried out periodically and in a structured manner. From the description above, it is concluded that it is necessary to improve the quality and procedures in the process of coaching the Lampung rock climbing sport.